Perancangan Aplikasi Pengolahan Data Posyandu Pada Posyandu Desa Cijantra Legok Berbasis Web - Adi Bayu Prakoso; Bagas Setiyaki Wicaksono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The application of data processing systems is needed in various fields, both in government agencies, education, private sector, education, health and other businesses. One of the services in the health sector in the community is posyandu. The problem that occurs in the posyandu griya in the village of cijantra legok is that the process of recording and processing data is still done manually, causing many obstacles in the processing, searching, and reporting of activities of the Griya Posyandu. So far, the reporting process that occurs at the Posyandu Griya is still not computerized, namely by re-recording the results of the examination from the medical record to the visit book one by one. Therefore, a posyandu data processing application was made in the village of Cijantra, Legok. The manufacture of this application used PHP and MySQL as the database media. The results of making this application provide convenience for cadres in minimizing the possibility of duplicate data errors in the process of processing, searching, and making reports on Posyandu Griya activities. The results of making this application make posyandu data processing at this web-based posyandu griya can provide effectiveness and improve work efficiency in processing data and making reports on posyandu activities.